Structure-Based Virtual Screening for Defeating Drug Resistant Form of EGFR Protein - Sharifi, Amirhossein; Bagherzadeh, Kowsar; Golestanian, Sahand; Amanlou, Massoud (Combinatorial Chemistry & High Throughput Screening, 2016)
Epidermal growth factor receptor (EGFR) is a tyrosine kinase with a key role in cell proliferation, death and differentiation. Mutations in EGFR, including substitution of Thr790 by methionine and Leu858 by arginine (T790M/L858R), lead to a lung cancer that is resistant against first generation inhibitors. In fact, second generation inhibitors were developed, but they proved to have had severe side effects because of the significant potency to suppress the wild type protein just as much. To resolve the problem, a step-by-step rational virtual screening was employed over almost sixty million compounds of PubChem Compound Database to filter out selective inhibitor(s) of T790M/L858R subtype. Consequently, the compound CID 133077 was observed, an active metabolite of Axitirome and also a cholesterol lowering prodrug. Selecting this compound can be explained by the oxamic acid part of molecule. Hence, administration of Axitirome or other compounds which contain oxamic acid is suggested in cases with EGFR T790M/L858R drug resistance.
Keywords: pharmacophore search